2018
DOI: 10.1212/nxi.0000000000000508
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl fumarate as a first- vs second-line therapy in MS

Abstract: ObjectiveTo elucidate the immunomodulatory effects of dimethyl fumarate (DMF) on B cells in patients with relapsing MS receiving DMF as a “1st-line” vs “2nd-line” therapy.MethodsB cells were isolated from 43 patients with MS at baseline and after 15-week DMF therapy. Phenotype and functional markers and cytokine profile were assessed by flow cytometry. Analysis included clinical and MRI parameters recorded during a 1-year follow-up.Results1st-line and 2nd-line patients presented several differences in their ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
(64 reference statements)
1
10
0
Order By: Relevance
“…9,27,28,36 Other DMTs had an impact on immune cell profile. Thus, as already reported, CD8 + T cells 31,37 and B-reg and B-memory cells 11,25 were affected by DMF treatment. The limited use, in our cohort of patients, of DMTs that more recently entered the market in Europe did not allow us to obtain enough information on B cell-depleting agents and on cladribine.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…9,27,28,36 Other DMTs had an impact on immune cell profile. Thus, as already reported, CD8 + T cells 31,37 and B-reg and B-memory cells 11,25 were affected by DMF treatment. The limited use, in our cohort of patients, of DMTs that more recently entered the market in Europe did not allow us to obtain enough information on B cell-depleting agents and on cladribine.…”
Section: Discussionsupporting
confidence: 84%
“…Altered levels and/or functional abnormalities in T or B cells have already been reported in patients with MS. 12,[19][20][21] However, previous studies are generally characterized by several limitations, including the focus on particular restricted immune cell subsets, small groups of patients mainly treated with a single DMT, 11,[22][23][24][25][26][27][28][29][30][31] different disease characteristics, lack of inclusion of controls, and difficult standardization of sample processing. 5,13,15,16 In this study, we have undertaken a large multicentric analysis of the immunologic profile of T and B cells in a cohort of 227 patients with MS at different disease stages treated with different DMTs and 82 HCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Most patients with FTY-PML were treated with FTY for >2 years and did not report severe lymphocytopenia. 27,28 The pharmacological effects of DMF are different from FTY, and it is no wonder that the decreased number of CD4/62L cells will not be a biomarker of the beneficial effects of DMF. Most lymphocytes causing inflammation in the central nervous system of patients with MS were included in the CD4/62L cell fraction.…”
Section: Discussionmentioning
confidence: 99%
“…15 It was also reported that the CD4/62L cell population was increased in patients treated with DMF by inducing the nuclear factor (erythroidderived 2)-related factor 2 pathway, which downregulates the nuclear factor-jB pathway. 27,28 The pharmacological effects of DMF are different from FTY, and it is no wonder that the decreased number of CD4/62L cells will not be a biomarker of the beneficial effects of DMF. In addition, the function of CD4/62L cells, including eliminating the John Cunningham virus, remains only partially understood; however, gradual intermittent drug holidays with CD4/62L cells used as a biomarker are useful to prevent excessive FTY administration or disease relapse.…”
Section: Discussionmentioning
confidence: 99%